Combination of Tumor Mutational Burden and Specific Gene Mutations Stratifies Outcome to Immunotherapy Across Recurrent and Metastatic Head and Neck Squamous Cell Carcinoma - Peng, Ying-Peng; Wang, Rong; Liu, Qiao-Dan; Xu, Xi-Wei; Wei, Wei; Huang, Xiao-Tao; Peng, Xiao-Mou; Liu, Zhi-Gang (Frontiers in Genetics, 2021)
Purpose: To investigate the prognostic significance of tumor mutational burden (TMB) combined with specific prognosis related gene mutations in immunotherapy for recurrent and metastatic head and neck squamous cell carcinoma (r/m HNSCC). Methods: One hundred and thirty-two r/m HNSCC patients from the Morris and the Allen cohorts had undergone immunotherapy. We constructed the immunotherapy related gene prognostic index TP-PR combining TMB and PIK3CA, TP53 or ROS1 mutation. And analyzed the differences in overall survival (OS) and immune cell infiltration between samples in different groups. The association of each signature’s single sample gene set enrichment analysis scores with TP-PR was tested using the Spearman correlation test. Results: The median OS of the patients with high TMB (TMB ≥ 10 mut/Mb) who received immunotherapy for r/m HNSCC was 2.5 times as long as that of the patients with low TMB (25 vs. 10 months). More importantly, high TP-PR (TP-PR>0) group had better median OS (25 vs. 8 months) than low TP-PR (TP-PR≤0) group. CD8+ T cells and activated memory CD4+ T cells in the tissues of the patients with high TP-PR was higher than that in the patients with low TP-PR. Results showed that TP-PR stratification had higher AUC value (0.77,95% CI 0.86-0.68) compared to TMB stratification (0.56,95% CI 0.68-0.44). The differential gene expression in high and low TP-PR groups mainly influenced metabolism-related signaling pathways. Conclusion: TP-PR was an effective predictor of immunotherapy outcome for r/m HNSCC, which might be better than TMB alone. Patients with high TP-PR had a better survival benefit compared with the patients with low TP-PR.